Resurgent Triads? Democratic mobilization and organized crime in Hong Kong - Varese, F; Wong, RWY (SAGE Publications, 2017)
On 3 October 2014, peaceful pro-democracy protestors were attacked by thugs in Mong Kok, a working-class neighbourhood of Hong Kong. Using this event, we explore whether the attackers came from the same neighbourhood and mobilized to protect their illegal business activities, and whether the attackers were affiliated to the Triads. We conclude that the attackers were low-level Triads affiliates from outside Mong Kok and were paid to attack the protesters. While several scholars have suggested that Triads are in inexorable decline in post-1997 Hong Kong, we suggest that they might have found a new role as enforcer of unpopular policies and repression of democratic protests in the context of a drift towards authoritarianism in Hong Kong. The paper is based on field interviews with Triad members, businesspeople and activists, and on press reports and official documents.